Biofilms of Candida albicans serotypes A and B differ in their sensitivity to photodynamic therapy - Rossoni, Rodnei Dennis [UNESP]; Barbosa, Junia Oliveira [UNESP]; Oliveira, Felipe Eduardo de [UNESP]; Oliveira, Luciane Dias de [UNESP]; Cardoso Jorge, Antonio Olavo [UNESP]; Junqueira, Juliana Campos [UNESP] (Springer, 2014)
Candida albicans is classified into different serotypes according to cell wall mannan composition and cell surface hydrophobicity. Since the effectiveness of photodynamic therapy (PDT) depends on the cell wall structure of microorganisms, the objective of this study was to compare the sensitivity of in vitro biofilms of C. albicans serotypes A and B to antimicrobial PDT. Reference strains of C. albicans serotype A (ATCC 36801) and serotype B (ATCC 36802) were used for the assays. A gallium-aluminum-arsenide laser (660 nm) was used as the light source and methylene blue (300 mu M) as the photosensitizer. After biofilm formation on the bottom of a 96-well microplate for 48 h, each Candida strain was submitted to assays: PDT consisting of laser and photosensitizer application (L + P+), laser application alone (L + P-), photosensitizer application alone (L-P+), and application of saline as control (L-P-). After treatment, biofilm cells were scraped off and transferred to tubes containing PBS. The content of the tubes was homogenized, diluted, and seeded onto Sabouraud agar plates to determine the number of colony-forming units (CFU/mL). The results were compared by analysis of variance and Tukey test (p < 0.05). The two strains studied were sensitive to PDT (L + P+), with a log reduction of 0.49 for serotype A and of 2.34 for serotype B. Laser application alone only reduced serotype B cells (0.53 log), and the use of the photosensitizer alone had no effect on the strains tested. It can be concluded that in vitro biofilms of C. albicans serotype B were more sensitive to PDT.
Keywords: Candida albicans; Photodynamic therapy; Methylene blue; Serotypes